SISTEM MAPEPEGAT DALAM UPACARA PERKAWINAN DI DESA BESAKIH RENDANG KARANGASEM - Negara, I Made Cakra; I Putu Sudarma; I Made Arsa Wiguna (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Three important aspects in a marriage ceremony: Religious aspects, social aspects and legal aspects. These three aspects are important because they relate to the harmonious relationship between Parhyangan, Palemahan and Pawongan in Hinduism called Tri Hita Karana. In Besakih Village, the validity of a marriage other than the three aspects above and the tri upasaksi, the validity of a marriage must go through a mapepegat system ceremony carried out in the first mandala of the Penataran Agung Besakih Temple. The mapepegat system is a point of becoming a member of the indigenous community. This study provides a deep understanding of cultural phenomena, traditions, and ceremonial systems without violating the integrity of the local community. Research results (1) Reasons for the mapepegat system: Historical and mythological, Preservation of tradition, Form of gratitude in the spiritual sense The right to become a member of the indigenous village community (2) Mapepegat procession: Ceremonial facilities fulfill the elements of satyam siwam sundaram Place and time of the ceremony in the first mandala of the Penataran Agung Besakih Temple, The ceremonial procession includes three stages The parties involved. tri upasaksi (3) Meaning of mapepegat: Philosophical language of the Veda yadnya, teachings of catur perumahan. Socio-religious, Theological. Aesthetics Harmony of macrocosm and microcosm. Keywords; Mapepegat System, Marriage Ceremony, Hindu Society.